A novel anti-ischemic nitric oxide donor inhibits thrombosis without modifying haemodynamic parameters - Vilahur, Gemma; Segalés, Estefania; Casaní, Laura; Badimon, Lina (Thrombosis and Haemostasis, 2004)
Platelets are involved in the clinical presentations of ischemic heart disease. Our objective was to study the antithrombotic effects of a new nitric oxide donor (LA419), a neutral sugar organic nitrate with a protected thiol group in its molecular structure. Animals were randomly distributed in three groups: I) oral administration of LA419 (0.9-1.8-3.6-5 mg/kg/d, 10 days); II) oral administration of standard IS-5-MN (0.9-1.8 mg/kg/d, 10 days); III) non-treated group (control). In catheterized pigs, thrombosis was studied under controlled rheological condi- tions by radioisotopic evaluation of deposited platelets on damaged vessel wall, placed in an extracorporeal perfusion chamber. Changes in blood pressure, heart rate, and platelet aggregation were evaluated. Results have shown that LA419 significantly decreased thrombus formation according to the degree of vascular damage, and shear rate conditions in a dose- dependent manner (p<0.005), without significant modifications on blood pressure and/or elevation of liver enzymes. In contrast, IS-5-MN only showed a significant reduction on plate- let deposition at the high dose, that was associated to hypoten- sion and elevation of liver enzymes. Therefore, we conclude that this new anti-ischemic NO-donor (NOd) LA419 that inhibits platelet function without modifying blood pressure may be a highly efficacious strategy to passivate platelet activation induced by a damaged vessel wall.
Keywords: Platelets; thrombosis; nitric oxide; blood pressure; pigs